2022
DOI: 10.24114/jpkim.v14i3.39788
|View full text |Cite
|
Sign up to set email alerts
|

The effect of argumentation-oriented learning models, inquiry-based learning models and science process skills on students' argumentation ability in chemistry

Abstract: One of the models whose learning syntax matches the science process skill component and students' argumentation ability is the inquiry model. Inquiry models have been widely applied, such as Guided Inquiry Based Learning (GIBL), and modified, such as the Argument Driven Inquiry (ADI) and Argumentative Inquiry Blended Learning (AIBL) learning models, where the ADI and AIBL learning models in the learning syntax have been integrated with argumentation activities. The purpose of this study was to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When the related literature is examined, it is found that argument-driven inquiry increases learners' academic achievement (Arslan, Genç, & Durak, 2023;Kaçar & Balım, 2021b;Sampson & Gleim, 2009;Walker et al, 2012) and improves their scientific research skills (Fitri, Rusdi & Effendi-Hasibuan, 2022;Walker & Sampson, 2013). Moreover there are studies on the effects of cognitive apprenticeship on learners' scientific inquiry (Aydemir, Baksa, & Skinner, 2011), their understanding of the nature of science (Bell, Blair, Crawford, & Lederman, 2003), and their cognitive-personal and professional development (Hunter, Laursen, & Seymour, 2007).…”
Section: Cognitive Apprenticeshipmentioning
confidence: 99%
“…When the related literature is examined, it is found that argument-driven inquiry increases learners' academic achievement (Arslan, Genç, & Durak, 2023;Kaçar & Balım, 2021b;Sampson & Gleim, 2009;Walker et al, 2012) and improves their scientific research skills (Fitri, Rusdi & Effendi-Hasibuan, 2022;Walker & Sampson, 2013). Moreover there are studies on the effects of cognitive apprenticeship on learners' scientific inquiry (Aydemir, Baksa, & Skinner, 2011), their understanding of the nature of science (Bell, Blair, Crawford, & Lederman, 2003), and their cognitive-personal and professional development (Hunter, Laursen, & Seymour, 2007).…”
Section: Cognitive Apprenticeshipmentioning
confidence: 99%